Administration with carnosic acid alleviates the development of osteoarthritis by attenuating macrophage polarization-mediated inflammation and cartilage oxidative damage and degradation via regulating Nrf2/NF-kB axis - Yang, Yang; Ping, Wenwen; Xu, Jin; Yang, Rong (Frontiers in Immunology, 2026)
IntroductionOsteoarthritis (OA) is a common inflammatory degenerative joint disease characterized by deterioration of articular cartilage. Macrophages exert the important roles in cartilage damage and synovial inflammation in OA. Carnosic acid (CA) possesses critical function in multiple inflammatory diseases.MethodsMacrophages were treated with carnosic acid. Chondrocytes were incubated with conditioned medium (CM) from macrophages. Then, the effects on macrophage polarization were analyzed. The effects on chondrocyte oxidative injury, inflammation and extracellular matrix (ECM) metabolism imbalance were explored. Carnosic acid was administrated to Anterior cruciate ligament transection (ACLT)-constructed OA mice model. Then, the efficacy of carnosic acid in the progression of OA was further explored.ResultsCarnosic acid inhibited LPS-induced macrophage M1 polarization and enhanced IL-4-evoked macrophage M2-like polarization. Furthermore, conditioned medium (CM) from M1 macrophages induced chondrocyte oxidative injury, which were abrogated by carnosic acid. Concomitantly, carnosic acid restrained M1 macrophage CM-increased inflammatory mediator and inflammatory cytokine IL-6 and TNF-α contents. Moreover, carnosic acid also antagonized M1 macrophage CM-evoked extracellular matrix (ECM) degradation. Mechanistically, carnosic acid enhanced Nrf2 expression and suppressed subsequent activation of the NF-κB signaling. Intriguingly, Nrf2 inhibition restrained activation of the NF-κB signaling and reversed carnosic acid-mediated suppression on macrophage M1-like polarization. Furthermore, carnosic acid attenuated M1 macrophage-induced oxidative injury, inflammatory response and ECM metabolism disturbance of chondrocytes. In vivo, carnosic acid alleviated articular cartilage degeneration and synovitis, leading to decrease of Osteoarthritis Research Society International (OARSI) and synovitis scores. Moreover, carnosic acid attenuated oxidative stress injury and cartilage degradation in OA mice. Additionally, carnosic acid affected synovium macrophage polarization from M1 to M2 , mitigated inflammation and activation of the Nrf2/NF-kB axis in OA mice.DiscussionCarnosic acid may alleviate the progression of OA by attenuating macrophage polarization-mediated inflammatory response and cartilage oxidative damage via regulating Nrf2/NF-kB axis, supporting it as a promising and potential therapeutic agent for patients with OA in clinical practice.